2012
DOI: 10.3109/14767058.2012.668588
|View full text |Cite
|
Sign up to set email alerts
|

Maternal autonomy on health in a community as assessed by signing of consent for caesarean section and its sociodemographic correlates

Abstract: The level of maternal autonomy on reproductive health issues based on this simple survey is less than satisfactory. However, this study has provided baseline data for surveillance and follow-up studies of this important variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Studies of women’s autonomy in developing countries first emerged in the context of reproductive health, women’s nutritional status and child health outcomes (immunization and nutrition) (Gage, 1995; Al Riyami et al ., 2004; Becker et al ., 2006; Acharya et al ., 2010; Thapa & Neihof, 2013). In contrast, few studies (Kritz & Makinwa-Adebusoye, 1999; Enabudoso & Igbarumah, 2012) have focused on women’s decision-making autonomy in the context of their own health care needs that are unrelated to reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of women’s autonomy in developing countries first emerged in the context of reproductive health, women’s nutritional status and child health outcomes (immunization and nutrition) (Gage, 1995; Al Riyami et al ., 2004; Becker et al ., 2006; Acharya et al ., 2010; Thapa & Neihof, 2013). In contrast, few studies (Kritz & Makinwa-Adebusoye, 1999; Enabudoso & Igbarumah, 2012) have focused on women’s decision-making autonomy in the context of their own health care needs that are unrelated to reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…The papers in this review suggest paternalism, cultural and gender norms all undermine women's voluntariness because they facilitate the transfer of women's decision‐making power from themselves to their husbands, families, and HCPs 22,25,27,31,32 . Women affected by these barriers were more likely to have a low level of education and therefore, more likely to receive partial disclosure of information from HCPs and to have husbands and family consent on their behalf 22–25 . As a result, women's low level of education, paternalism, and cultural and gender norms are barriers to all three of Beauchamp and Childress's domains of informed consent.…”
Section: Discussionmentioning
confidence: 99%
“…22 A southern Nigerian study found women without a tertiary education were more likely to hold the belief that men, as heads of families, should make the decision to have a CS on their behalf compared with women with a tertiary education. 23 Malawian and Tanzanian studies found women with low levels of education were uninformed about their rights and, therefore, expected…”
Section: Low Level Of Educationmentioning
confidence: 99%
See 2 more Smart Citations